TRANSCATHETER AORTIC VALVE IMPLANTATION. STATE OF THE PROBLEM AND PROSPECTS IN RUSSIA - T. E. Imaev; A. E. Komlev; R. S. Akchurin (Столичная издательская компания, 2015)
Nowadays aortic stenosis is the most common valvular pathology in Europe and North America and its incidence increases with age. Long asymptomatic period, the duration of which varies in different patients, is the main clinical feature of this disease. In 80% of asymptomatic patients with the severe aortic stenosis the onset of clinical signs that significantly worsen the prognosis, occurs within the next 4 years. So, if two-year survival rate in asymptomatic period is at least 50%, a 5-year survival rate in patients with symptomatic aortic stenosis without surgery, according to some estimates, is reduced to 15%. Therefore, these patients do not have any alternative to surgery. At that, high risk of complications after surgery and perioperative mortality related to them are the most essential problems of surgical treatment of the aortic valve diseases in the setting of cardiopulmonary bypass. This was the decisive factor for the development of alternative methods of surgical correction of the aortic valve diseases. Indications and contraindications for transcatheter aortic valve implantation (TAVI), which is currently a "disruptive technology", are discussed. Different models of aortic valve prostheses, the use of which is confirmed by the available evidence, are considered. The most important unsolved problems of TAVI use in recent times are mentioned in brief. More than 300 TAVI procedures have been performed in Russia recently which definitely does not cover the actual needs.